Simulation-based training in transitions from school to workplace learning - Vibe Aarkrog (Scandinavian Journal of Vocations in Development, 2024)
The article concerns the impact of simulation-based training (SBT) on students’ transition from school-based to workplace-based training in Danish social and healthcare programmes. Denmark has a dual system of vocational education and training, and these transitions are associated with significant dropout. To facilitate the students’ transition, teachers and trainers developed a five-day SBT course conducted in workplaces (care homes). An affiliated research project studied the impact of SBT on how students experienced this transition.